Stratigraphy of the middle Triassic-lower Cretaceous succession in the Paraná and Uruguayan Chaco-Paraná Basins – An overview based on subsurface data - de Paula e Silva, Flávio [UNESP]; Caetano-Chang, Maria Rita [UNESP]; Chang, Hung Kiang [UNESP] (Elsevier, 2023)
The Middle Triassic to Lower Cretaceous (MTLC) megasequence of the Paraná and Uruguayan Chaco-Paraná basins records a complex depositional history. It encompasses a dynamic interplay of continental lacustrine, fluvial, and aeolian sediments that have evolved under varying paleoenvironmental and climatic conditions, ranging from humid to arid and hyper-arid settings. The present subsurface study depicts a novel stratigraphic framework for the MTLC megasequence, drawing from an extensive dataset of over 400 well logs and drilling reports derived from exploratory petroleum and water wells distributed across these basins. The lithostratigraphic units within the MTLC megasequence, as delineated from the well logs, exhibit a consistent stacking pattern with well-defined hierarchic arrangement, which extends throughout the Paraná and Chaco-Paraná basins. Within the MTLC megasequence, three distinct sedimentary successions have been established, bounded by regional unconformities: the Middle to Upper Triassic sequence, the Upper Jurassic sequence, and the Lower Cretaceous sequence. The Middle to Upper Triassic sequence encompasses the Santa Maria/Caturrita, Piramboia, and Itacumbú formations. The Santa Maria/Caturrita sequence extends into the subsurface to Uruguay, where it is referred to as the Itacumbú Formation. The Piramboia Formation has been subdivided into two distinct units: the lower unit retains the name Piramboia Formation, while the upper unit has been designated as the Guará Formation, as it was originally defined in the Rio Grande do Sul State. The Upper Jurassic sequence encompasses the Guará and Tacuarembó formations, extending throughout the entire Paraná and Uruguayan Chaco-Paraná basins. The Lower Cretaceous sequence comprises the Botucatu and Rivera formations. These deposits are generally discontinuous and frequently intercalated with the volcanic rocks of the Serra Geral Formation.
Keywords: Guará formation; Middle Triassic to lower cretaceous negasequence; Paraná basin; Piramboia formation; Uruguayan Chaco-Paraná Basin; Well logs